Dinamika Tim Tagihan dalam Distribusi Surat Pemberiatahuan Bayar Pajak di Samsat Kota Tanjungpinang - Firmansyah, Muhammad; Safitri, Nur Aprilia; Sikin, Muhamad (Universitas Muhammadiyah Enrekang, 2023)
The research aims to find out what are the problems of UPTD PDD Tanjungpinang team in distributing SPSOPKB to the taxpayer. Based on the contribution of Riau Islands Provincial Native Income to the Budget, it is still necessary to increase, given that we are still dependent on the Central Government Perimbangan Fund. As for the method used in data collection, observation (observation). The Regional Revenue Manager of Tanjungpinang performs efforts to increase tax revenue by carrying out the activities of Control, Inspection, and Supervision of Regional Taxes by involving several relevant Agencies in Tanjungpinang. From the results of the research there are several problems faced by the responsible team such as incomplete data, taxpayer addresses not being found, vehicle status unclear, and waiting for financing. However, efforts continue to be made by UPTD PPD Tanjungpinang so that tax revenue can continue to be actively carried out such as requiring taxpayers to report personal data, adding tax exemption programs, improving Tax Application data, providing liability letters in motor vehicle tax handling, and optimizing computer performance. Tax exemption efforts continue to be actively carried out by UPTD PPD.